Impact of traditional East Asian medicine as an add-on therapy on survival and recurrence after surgery for breast cancer: A systematic review and meta-analysis - Jee-Hyun Yoon; Eun Hye Kim; Su Bin Park; Hayun Jin; Seong Woo Yoon (Frontiers in Pharmacology, 2023)
Background: Breast cancer is the most common cancer in women. Patients with cancer increasingly incorporate complementary and alternative medicines, including traditional East Asian medicine (TEAM), for cancer prevention and treatment. This review aimed to determine the effectiveness and safety of TEAM for survival and recurrence after surgery in patients with breast cancer.Methods: We searched nine electronic databases up to 25 August 2022, for randomized controlled trials (RCTs) of TEAM to prevent the recurrence of breast cancer in female patients after mastectomy or breast-conserving surgery. The primary outcome was 5-year disease-free survival (DFS), and secondary outcomes were 5-year overall survival, locoregional and distant recurrence rates, and toxicity. This study adhered to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to evaluate the quality of evidence.Results: From 368 citations, data from nine studies reporting on a total of 1240 patients were included in the systematic review, and eight studies were deemed suitable for the meta-analysis. TEAM combined with adjuvant chemotherapy showed a significant improvement in DFS (odds ratio [OR] 0.42%, 95% confidence interval [CI] 0.28 to 0.61, p < 0.00001) and overall survival (OR 0.44%, 95% CI 0.27 to 0.73, p = 0.001) compared to adjuvant chemotherapy alone. The reduction in the rate of total recurrence was favorable for TEAM combined with adjuvant chemotherapy compared to adjuvant chemotherapy alone (Risk ratio 0.49%, 95% CI 0.35 to 0.70; p < 0.0001). TEAM after adjuvant chemotherapy showed a significant advantage in DFS compared to no TEAM (OR 0.61%, 95% CI 0.41 to 0.92, p = 0.02). No severe adverse events related to TEAM were reported. The overall certainty of the evidence for DFS, overall survival, and the total recurrence rate were moderate when postoperative breast cancer patients used TEAM combined with adjuvant chemotherapy.Conclusion: Moderate-quality evidence suggests TEAM as an add-on therapy to adjuvant chemotherapy. TEAM may have the potential to improve long-term survival and prevent postoperative recurrence in patients with breast cancer. In future, more rigorous RCTs should be conducted to confirm these findings.